Local Democracy And The Processes Of Transformation In East-central Europe - Baldersheim, Harald, 1944-; Illner, Michal; Offerdal, Audun; Rose, Lawrence E., 1944-; Swianiewicz, Paweł (Urban policy challenges., 2019)
This book focuses on one particular aspect of the post-communist transformations in the East-Central European countries. In studying the local government reforms, it evaluates achievements with the traditional yardsticks for local government performance: democracy, efficiency, and autonomy.